Integrating Pauline Ethics into Character Education: A Four-Pillar Framework for Advancing SDG 4 in Effective 21st-Century Schools - Layu Marsiana; Erny Roesminingsih; Karwanto Karwanto (Journal of Current Studies in SDGs, 2026)
Objective: To examine the integration of Pauline Ethics into character education through a Four-Pillar Model designed to strengthen effective 21st-century schools amid increasing moral, social, and digital challenges. The study aims to analyze the implementation of Pauline Ethics-based character education and its contribution to supporting SDG 4 (Quality Education) through holistic character development. Method: Employing a qualitative case study approach in a private junior high school in Indonesia. Data were collected through in-depth interviews, participatory observation, and document analysis involving school leaders, teachers, and students. The collected data were analyzed using thematic analysis to identify patterns related to the implementation of Pauline Ethics values. Results: The findings indicate that the values of Regularité, Simplicité, and Travail were effectively internalized through four interconnected pillars: curricular integration, teacher role modeling, school culture, and ecosystem collaboration. These pillars contributed to strengthening students’ discipline, responsibility, empathy, perseverance, and twenty-first-century competencies while fostering a supportive and value-oriented school environment. Novelty: Introducing the Pauline Ethics Four-Pillar Model as a novel spiritually grounded character education framework that systematically integrates curriculum, teacher role modeling, school culture, and educational ecosystem engagement. The model provides a practical and contextual approach for strengthening character formation and promoting quality education in contemporary schools.